Inventory of Local Fruit Plants in Badang Village, Jombang Regency - Yuliana, Anggi Indah; Nasirudin, Mohamad; Mahfudin, Sayyid (LPPM Universitas KH. A. Wahab Hasbullah, 2024)
Badang Village is one of the areas in Jombang Regency that has the potential for yards that are rich in biotic resources, one of which is fruit plants. This study aims to determine the diversity of fruit plant species in the yard area of Badang Village residents. This research was conducted from February to June 2022 in Badang Village, Ngoro District, Jombang Regency. The results showed that there were 22 types of fruit plants scattered in 6 hamlets of Badang Village, Ngoro Subdistrict, Jombang Regency, including: avocado, star fruit, durian, guava, orange, katilayu, longan, kersen/keres, mango, pineapple, jackfruit, papaya, banana, rambutan, salak, date palm, mustard, soursop, dragonfruit, grape, red pomegranate and sugar apple. The index of fruit plant diversity in Badang Village for each hamlet is different, for Badang Hamlet the diversity index value is 2.111, Wates Hamlet is 2.049, Wonoasri Hamlet is 1.973, Sukotirto Hamlet is 1.682, Wedani Hamlet is 1.443. The five hamlets are categorized as having a moderate diversity index. As for Watulintang Hamlet, the diversity index value is 0.957, so it is classified as low compared to other hamlets.